Fruit size, yield and nutritional quality in tomato: implications of elevated CO2 and temperature - Pimenta, Thaline Martins (2021)
The atmospheric concentration of carbon dioxide (CO2 ) has increased and it could reach 1000 ppm by the end of the century. Associated with these changes, global warming occurs progressively. These factors, elevated CO2 concentration and high temperature, are expected significantly to affect the growth, yield and quality of crops consumed worldwide. Thus, we investigated the effect of elevated CO2 in determining fruit size, yield and nutritional quality in natural warming scenarios (Chapter 1). In addition, we investigated how high CO2 acts in modulating the size and ripening of tomato fruits (Chapter 2). Our results show that the effects of high CO2 on fruit yield and composition depend on plant growth temperature. In general, these factors increased the fruit fresh weight, diameter and fruit yield, however the nutritional quality was impaired. Fruits under elevated CO2 concentration at higher temperature showed reduction of lycopene, β-carotene, ascorbic acid, Zn and Mg greater than fruits under ambient CO2 . Furthermore, heating reduced the brix, soluble sugars, total phenols and fruit dry mass, regardless of the CO2 condition. The increase in fruit size under elevated CO2 was related to greater availability of carbon, which provided higher growth rate. Fruit growth was modulated by greater expansion of pericarp cells, increased expression of expansin genes and nutrient concentration in fruits under high CO2 . The increase in fruit size resulted in hasty ripening. This result was associated with an increase in the concentration of carotenoids, greater ethylene production and expression of ethylene biosynthesis and signaling genes. This study brings new perspectives regarding the action of elevated CO2 in combination with warming air temperature in determining fruit yield and nutritional quality, as well as how elevated CO2 can act to modulate fruit size and ripening under future environmental conditions. Keywords: CO2 enrichment. Fruit mineral composition. Warming. Fruit development. Carotenoids. Cell expansion.